2014
DOI: 10.1080/02640414.2014.989534
|View full text |Cite
|
Sign up to set email alerts
|

Acute effect of different minimalist shoes on foot strike pattern and kinematics in rearfoot strikers during running

Abstract: Despite the growing interest in minimalist shoes, no studies have compared the efficacy of different types of minimalist shoe models in reproducing barefoot running patterns and in eliciting biomechanical changes that make them differ from standard cushioned running shoes. The aim of this study was to investigate the acute effects of different footwear models, marketed as "minimalist" by their manufacturer, on running biomechanics. Six running shoes marketed as barefoot/ minimalist models, a standard cushioned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
74
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(89 citation statements)
references
References 22 publications
4
74
4
Order By: Relevance
“…They suggested that minimalist shoes with a smaller heelstack height (7À13 mm) were more likely to change running biomechanics than minimalist shoes with a greater stack height (22À26 mm) because the latter provides more protection for the heel and allows a more comfortable RF. 5 However, contrary to this finding, the minimalist shoes in our study had a heel-stack height of 22 mm and still caused runners to alter the strike index and ankle angle. Therefore, the effects of minimalist shoes on foot-strike pattern may not be explained solely by differences in heel-stack height.…”
Section: Discussioncontrasting
confidence: 88%
See 4 more Smart Citations
“…They suggested that minimalist shoes with a smaller heelstack height (7À13 mm) were more likely to change running biomechanics than minimalist shoes with a greater stack height (22À26 mm) because the latter provides more protection for the heel and allows a more comfortable RF. 5 However, contrary to this finding, the minimalist shoes in our study had a heel-stack height of 22 mm and still caused runners to alter the strike index and ankle angle. Therefore, the effects of minimalist shoes on foot-strike pattern may not be explained solely by differences in heel-stack height.…”
Section: Discussioncontrasting
confidence: 88%
“…Fourth, we investigated only 1 type of minimalist shoe. The shoe mass, heel drop, and stack height of the racing flat used in our study were equivalent to those of several other minimalist shoes ( 5 Nonetheless, racing flats have been used by runners for many years and can be considered representative of the running footwear used before the introduction of modern conventional running shoes. 11,17 Therefore, racing flats are well suited to investigations of minimalist footwear.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations